Specifications for a Laboratory for Mr. F.C. Turner, Berkeley, California, May, 1938 - Julia Morgan::::::author::: (1938)
Specifications produced by architect Julia Morgan's practice. Includes specifications for general conditions, excavating and grading, masonry, plastering, carpentry, metal work, roofing, painting, plumbing and electrical work for the laboratory.